PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN MEDIA MIND MAPPING TERHADAP HASIL BELAJAR IPAS SISWA KELAS V DI SDN GUGUS VI KECAMATAN GEROKGAK - Parmiti, Ni Luh Dita Parmiti; Tristaningrat , Made Adi Nugraha; Adnyana, Komang Surya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of fifth-grade elementary school students in Cluster VI, Gerokgak District, which is caused by the dominance of conventional learning and the minimal use of interactive media. The purpose of this study is to analyze the impact of implementing the Discovery Learning model assisted by Mind Mapping media on improving science learning outcomes. The study used a quantitative approach with a quasi-experimental type and a Pretest-Posttest Control Group Design. The sample consisted of 21 fifth-grade students of SDN 31 Pemuteran as the experimental group and 22 fifth-grade students of SDN 2 Pemuteran as the control group. The results of the independent t-test analysis showed t-count (7.133) > t-table (1.683) with Sig. (2-tailed) = 0.000 < 0.05, so there was a significant difference in science learning outcomes between the two groups. The N-Gain value of the experimental group was 54.45% (quite effective) far exceeding that of the control group of 3.72% (ineffective).